The Avalokiteśvara Cult in Turfan and Dunhuang in the Pre-Mongolian Period - Kasai, Yukiyo (Dynamics in the history of religions, 2022)
The art objects and written sources found in the Turfan area show the devout worship of various bodhisattvas by the Buddhists who lived in this region. The Uyghurs were undoubtedly one of the most influential groups there. Chinese Buddhist impact from Dunhuang became an essential factor for the Uyghurs after most of them converted to Buddhism. Some scriptural sources in Old Uyghur had a close relationship with their Chinese versions widespread in Dunhuang. Thus, there were exchanges between Buddhist communities in Dunhuang and Turfan through which some buddha and bodhisattva cults were probably shared. One of those cults was that of the Bodhisattva Avalokiteśvara. In Dunhuang, one has both written and figurative sources that show the relevance of the Avalokiteśvara cult. Significantly, the Chinese prayer texts describe Avalokiteśvara as a saviour from diseases and guide to paradise. In Turfan, on the contrary, the written sources in Old Uyghur neither focus on the cult nor refer to any of this bodhisattva’s roles mentioned above, although many banner paintings in Turfan were devoted to Avalokiteśvara. The gap of this bodhisattva’s appearance in the written and artistic sources from Turfan is thought to be due to that both Uyghurs and Chinese involved in Buddhist activities. The cult of Avalokiteśvara, which was strongly impacted by Chinese Buddhism, was probably represented in both the Chinese Buddhist community in Turfan and the Uyghur Buddhists, who had a close connection to that community.